Vision(s) de la littérature québécoise en Italie. Révisions nécessaires? - Acerenza, Gerardo (Romanica Silesiana, 2020)
Literary texts written in French-speaking areas out of France very often represent real challenges for translators, because they have to deal with a diatopically marked language and with a large number of realia which require the implementation of specific strategies for translate in the target language. In this article, we will try to understand the strategies used by Italian translators when translating the linguistic specificities of Quebec literary works in Italian. The practice of translation can orient the vision (or reception) of a Quebec literature in Italy which appears at first sight to be hermetic because of its linguistic regionalisms. Do Italian translations of Quebec literature require revisions?